Urethral Steinstrasse following Laser Lithotripsy of Prostatic Urethral Calculi - Den, Jennifer (Case Rep Urol, 2018)
Symptomatic prostatic calculi are rare occurrences with several management options, the most popular of which is currently transurethral laser lithotripsy. This is a generally well-tolerated procedure with minimal complications. To date, no reported episodes of steinstrasse at the urethral level following prostatic calculi lithotripsy have been documented to our knowledge. We report a unique case of acute urinary retention secondary to obstructive calculi fragments following a transurethral laser lithotripsy of large prostatic calculi, further complicated by stricture at the fossa navicularis.